دراسة تأثر ارتباط وجوه الراتنج المركب المباشرة )الكومبوزت( مع الميناء السنية من خلال تطبيق التبييض المنزلي (Latakia University Journal -Medical Sciences Series, 2014)
تألفت عينة البحث من 80 ثنية سليمة ومقلوعة تم الحصول عليها من العيادات الخاصة وقسم الجراحة  ، وقد قسمت إلى مجموعتين اثنتين متساويتين، تم استخدام المادة الرابطة ClearFil SE Bond في واحدة منهما وتم استخدام المادة الرابطة OptiBond Solo Plus  في الأخرى، وقسمت كل مجموعة إلى أربع مجموعات فرعية متساوية تم تطبيق الوجوه في الأولى منها دون إجراء أي تبييض للأسنان، وتم تطبيق الوجوه في الثانية قبل التبييض بأسبوعين وتم تطبيق الوجوه في الثالثة بعد التبييض مباشرة وتم تطبيق الوجوه في الرابعة بعد التبييض بأسبوعين, وكان الهدف من ذلك  دراسة تأثير تبييض الأسنان المنزلي باستخدام فوق أوكسيد الكارباميد تركيز16 %على ارتباط وجوه الراتنج المركب الضوئية التصلب مع الميناء السنية وذلك بمقارنتها مع العينات الشاهدة غير المعرضة للتبييض وذلك خلال فترات محددة . تم وضع الأسنان في أسطوانات معدنية من خلال تثبيتها في قوالب أكريلية وقد تم فحص الارتباط . والنتيجة أن هناك دلالة إحصائية ما بين العينة الشاهدة والمجموعة الأولى التي تم فيها إجراء الوجوه قبل إجراء التبييض بأسبوعين . The research project sample consisted of 80 extracted central incisors obtained from the Oral and Maxillofacial Surgery Department as well as from private practices. These teeth were divided into two equal groups. The bonding agent ClearFil SE Bond® was used in one group, whereas the OptiBond Solo Plus® bonding agent was used in the other group. Each group was divided into four subgroups: (1) veneers performed without any bleaching, (2) veneers performed two weeks before bleaching, (3) veneers performed immediately following bleaching and (4) veneers performed two weeks after bleaching. veneers were made using a special template which allowed producing the same size of all the specimens used in this project. These veneers were placed on the vestibular surfaces of enamel of the extracted central incisors. The aim of the previous procedures was to study the effect of home teeth bleaching . Teeth were embedded in acrylic blocks created in metallic cylinders. The bonding strength was measured through . The results showed that there was a significant difference between the control subgroup and the second subgroup .